2018
DOI: 10.1027/1016-9040/a000334
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Integration of Three Key Components of Identity Development

Abstract: Abstract. Studies on identity formation focus on various components of identity. However, these components have mainly been studied separately, and researchers in different fields are not always aware of each other’s work. Therefore, this systematic review provides an overview of theories and empirical studies on three key components of identity: distinctiveness (seeing the self as unique and distinct from others), coherence (perceiving the self as similar across life domains), and continuity (perceiving the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 67 publications
3
55
0
3
Order By: Relevance
“…Yet, our findings also showed that compared to commitment, general distinctiveness was in quite some cases an equally strong marker and for some aspectssocial well-being and self-esteemeven had incremental predictive value. Our findings validate the strong focus on commitments in studies on identity formation (see Meeus, 2011;Van Doeselaar et al, 2018), but also indicate that an adaptive identity not only consists of strong commitments. So far, studies focusing on different adaptive identity features have been rare (see Van Doeselaar et al, 2018), and our findings…”
Section: Distinctiveness Versus Commitmentsupporting
confidence: 84%
See 1 more Smart Citation
“…Yet, our findings also showed that compared to commitment, general distinctiveness was in quite some cases an equally strong marker and for some aspectssocial well-being and self-esteemeven had incremental predictive value. Our findings validate the strong focus on commitments in studies on identity formation (see Meeus, 2011;Van Doeselaar et al, 2018), but also indicate that an adaptive identity not only consists of strong commitments. So far, studies focusing on different adaptive identity features have been rare (see Van Doeselaar et al, 2018), and our findings…”
Section: Distinctiveness Versus Commitmentsupporting
confidence: 84%
“…Adaptive identity formation can thus likely be conceptualized as a cluster of related features, such as a sense of general distinctiveness as well as strong commitments (Pasupathi, 2014;Van Doeselaar, Becht, Klimstra, & Meeus, 2018). To examine the role and importance of distinctiveness in the broader identity construct, we compared the nomological network of the two conceptualizations of distinctiveness to that of identification with commitment.…”
Section: Distinctiveness Versus Commitmentmentioning
confidence: 99%
“…By constructing their own personal identity, adolescents can obtain a sense of "progressive continuity between that which [they have] come to be during the long years of childhood and that which [they promise] to become in the anticipated future" (Erikson, 1968, p. 87). This sense of personal continuity is one of the key aspects of Erikson's conceptualization of an adaptive identity, which is THE NARRATIVE AND THE DUAL-CYLE APPROACH 35 still present in the narrative (McAdams, 2001) and dual-cycle approaches (Van Doeselaar, Becht, Klimstra, & Meeus, 2018). Moreover, both approaches also still recognize the importance of social (e.g., McLean & Jennings, 2012;Van Doeselaar, Meeus, Koot, & Branje, 2016) and cultural (e.g., McLean & Syed, 2015;Negru-Subtirica, Tiganasu, Dezutter, & Luyckx, 2017) contexts for identity formation.…”
Section: Erikson's Views On Identity Formationmentioning
confidence: 99%
“…Identity formation is conceptualized as a dual-cycle process of forming and evaluating identity commitments in various relevant domains, such as occupational aspirations (Crocetti, Rubini, & Meeus, 2008;Luyckx et al, 2006). Strong identity commitments are assumed to provide a sense of personal continuity as they provide a sense of direction and certainty regarding the future (Van Doeselaar et al, 2018). Dual-cycle models provide a more detailed approach to Marcia's (1966) original identity status framework.…”
Section: Dual-cycle Model Of Identity Formationmentioning
confidence: 99%
“…Também a investigação sobre individuação e formação da identidade vai no mesmo sentido da diferenciação e integração crescentes (Blos, 1968;Erikson, 1959). Alguns estudos têm efetivamente mostrado que o sentido de ser diferente dos outros (van Doeselaar, Becht, Klimstra, & Meeus, 2018), a exploração de diferentes identidades e a emergência de diferentes domínios identitários (Meeus, 2011) aumentam ao longo da adolescência. Contudo, no final da adolescência, a intervenção de habilidades integrativas que combinem essas diversas possibilidades psicossociais em compromissos identitários fortes parece ser importante para o bem-estar e a adaptação psicológica (Erikson, 1959;Meeus, 2011).…”
Section: Avanços Cognitivos Da Adolescência E Reorganização Do Autocounclassified